A holistic perception of foreign financing of developing countries' private sector: Analysis and descreption of structure and trends - Matthew Odedokun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper presents a comprehensive survey of the `shopping list' of sources of external finance that are directly channelled to the business sector of developing countries. Generally, our analytical survey covers the 1970-2000 period, and includes the distribution of foreign resources classified according to the different income-based and geographical breakdown of developing countries. We examine aggregate net resource flows in the form of the saving-investment gap and current account surplus in the balance-of-payments of developed countries. Also examined is the institutionalized component of this aggregate, which encompasses both official and private flows. In addition, we discuss the different components of private flows, including unrequited private transfers (grants by NGOs and workers' remittances) and commercial capital flows (private flows to multilateral institutions and bilateral private capital flows in the form of foreign direct investments and portfolio capital flows) to developing countries. Official foreign flows for business sector development are also discussed. The recent pre-occupation with assistance to microfinance and microenterprises in developing countries as a way of enhancing poverty reduction and gender balance in recipient countries is also highlighted. These official sources are bilateral and multilateral flows, including those from the International Finance Corporation. Items that are, by their nature, inherently net outflows from developing countries are also examined. These include the cross-border international banking transactions by residents of developing countries that often give rise to capital flight. Also included are the foreign currency and other liquid liabilities of developed countries, whose holding by the residents of developing countries seems be increasing.
Keywords: F21; F22; F32; F34; F35; O19; O24; 330; saving-investment gap; NGO grants; workers' remittances; private sector development; donors; private capital flows; international banking; capital flight; Kapitalmobilität; Privatwirtschaft; Entwicklungsländer